Biochemical compositions of black carpenter ant, Camponotus pennsylvanicus (Hymenoptedra : Formicidae) (Jahangirnagar University Journal of Biological Sciences, 2017)
Abstract not availableJahangirnagar University J. Biol. Sci. 6(1): 59-62, 2017 (June)